REINTERPRETASI HADIS LARANGAN MELUKIS DAN LARANGAN PEREMPUAN BEPERGIAN TANPA MAHRAM ( Hermeneutika Fazlur Rahman) - Ghufron Hamzah (Universitas Wahid Hasyim Semarang, 2019)
Abstract The standardization process (textualization-normative) and dynamization (contextualization-historical) of Islamic teachings must indeed go together so that the formula which states that Islam is